DAMPAK PENGADOPSIAN INTERNATIONAL FINANCIAL REPORTING STANDARDS TERHADAP TINGKAT ENVIRONMENTAL DISCLOSURE - , Eko Prasetyo Agustia, Arief Surya Irawan, SE., M.Com. ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The study aims to test the difference of environmental disclosure level before and after the adoption of International Financial Reporting Standards (IFRS). Nowadays, IFRS becomes hot issue discussed emerging in various countries. By using annual report and sustainability report as many as 20 manufacturing and mining firms obtained from the www.idx.co.id , this research compares between environmental disclosure level before (2010) and after (2012) the adoption of IFRS. This study uses purposive sampling and analysis techniques used in this research paired sample t-test. The result of this research shows that there is a significant difference in environmental disclosure level before and after the adoption of IFRS. Environmental disclosure level after adoption is higher than before adoption. The adoption of accounting standards to IFRS will increase the level of environmental disclosure.